Advancing radioactive material research method: the development of a novel in situ particle-attached microfluidic electrochemical cell - Yao, Jennifer; Tripathi, Shalini; McNamara, Bruce K.; Lahiri, Nabajit; Riechers, Shawn L.; Chatterjee, Sayandev; Reilly, Dallas D.; Ilton, Eugene S.; Buck, Edgar C. (Frontiers in Nuclear Engineering, 2023)
This describes the development of a vacuum compatible microfluidic electrochemical cell (E-cell) for investigating the redox behavior of uranium oxide (UO2). Experiments using bulk amounts of radioactive material can be costly and may require shielded hot cell facilities. In contrast, the amount of radioactive material used in a single test could be significantly reduced by using microfluidic techniques, allowing electrochemical experiments possibly to be conducted outside a shielded facility. We describe different approaches for building a microfluidic E-cell, that all use UO2 as the working electrode, with the ability to characterize the corroding materials in situ. We found that embedding UO2 particles in a polyvinylidene fluoride binder was the most effective method, and further demonstrated that particle-based electrodes can provide an effective and low-cost solution for microfluidic electrochemical applications. The in-situ microfluidic E-cell offers a promising method for investigating the corrosion of UO2 and other materials while reducing the amount of materials needed for analysis to microgram levels.